DESCRIPTION OF THE HISTORY OF THE SOMONID RULERS IN ABU BAKR NARSHAKHI'S "HISTORY OF BUKHARA" (Universal International Scientific Journal, 2026)
This article provides a brief overview of Abu Bakr Narshahi's work "History of Bukhara". The history of the Samanid state is covered in detail. The activities of the Samanid rulers in state administration are analyzed. The development policy of the city of Bukhara is extensively covered based on source studies.
Keywords: Somankhudot, Ismail Somoni Mausoleum, Hajib ul-hajib, Hajib ul-buzruk, palace checkers, Registan Square, master, Sheikh ul-Islam, dome of Islam, khanaqoh.